Gas adsorption in an isostructural series of pillared coordination cages. Issue 49 (6th June 2018) - Gosselin, Eric J.; Lorzing, Gregory R.; Trump, Benjamin A.; Brown, Craig M.; Bloch, Eric D.
Abstract : The synthesis and characterization of two novel pillared coordination cages is reported. Abstract : The synthesis and characterization of two novel pillared coordination cages is reported. By utilizing 1, 4-diazabicyclo[2.2.2]octane (dabco) as a pillar with increased basicity as compared to pyrazine or 4, 4′-bipyridine, a stable copper-based material was prepared. Extending this strategy to iron(ii ) afforded an isostructural material that similarly retains high porosity and crystallinity upon solvent evacuation. Importantly, the iron solid represents a rare example of porous iron paddlewheel-based metal–organic material that is stable to solvent evacuation. Neutron powder diffraction studies on these materials indicate the triangular and square windows of the cage are prime ethane and ethylene adsorption sites.